Adiponectin Receptor 1 and Liver Kinase B1 are Downregulated in Renal Cell Carcinoma - Beatty, Laura (My University, 2011)
Obesity is the latest epidemic of the 21st century. Indeed, numerous studies have associated obesity with an increased risk of developing several health conditions, including cancer. Moreover, modest increases in body mass index increase the risk of developing cancer, especially cancer of the kidney. Although the mechanism mediating this increased risk is unknown, the plasma level of adiponectin is known to be inversely correlated with body weight and risk of developing kidney cancer.
Tumour suppression via adiponectin is believed to be mediated through adiponectin receptor-1, which activates AMPK by LKB1 and suppresses pathways upregulated in cancer by inhibiting mTOR. Consistent with the anti-tumourigenic properties of this pathway, several cancers display reduced AdipoR1 and LKB1 expression and/or increased mTOR activity. In this study we identified reduced AdipoR1 and LKB1 protein expression in patients’ renal cell carcinomas and quantified the reduction in LKB1, on tissue microarrays containing 201 RCC patients, to be significant.
Targeted knockdown of LKB1 in CRL-1932 cells (shLKB1) was accompanied by a reduction in AdipoR1, and recapitulated our observations in RCC tumours. These shLKB1 cells were unable to execute established events of adiponectin-AMPK signalling and, presented increased proliferation and invasion abilities in vitro and tumour growth in vivo. Collectively, these results suggest that a reduced plasma level of adiponectin coupled with a downregulation of AdipoR1 and LKB1 expression, disrupts the tumour-suppressive adiponectin-AMPK signalling pathway, and rationalizes the association of obesity with the development of RCC.
Keywords: AdipoR1; LKB1; RCC; Medical Genetics; Medical Genetics